Strategic decision-making processes in internationalization: Does national culture of the focal firm matter? - Dimitratos, Pavlos; Petrou, Andreas; Plakoyiannaki, Emmanuella; Johnson, Jeffrey E. (My University, 2011)
We seek to examine how national culture values affect strategic decision-making processes (SDMPs) of internationalized firms. We employ the cultural relativity theory to explain how firms from different countries make international decisions. We advance hypotheses regarding the associations between three SDMP dimensions and three national culture aspects, notably the relationships between hierarchical decentralization and power distance; lateral communication and individualism; and, formalization and uncertainty avoidance. We present evidence from a large-scale study conducted on 528 internationalized small and medium-sized firms based in the USA, UK, Greece and Cyprus. The findings support our hypotheses with the exception of that concerning lateral communication and individualism. The national culture of the focal firm matters as far as SDMPs in internationalization are concerned. Implications and further research directions are discussed.
Keywords: Internationalization; Strategic decision-making process; National culture